Longitudinal drift of substorm electrons as the reason of impulsive precipitation events and VLF emissions - Lubchich, A. A.; Yahnin, A. G.; Titova, E. E.; Demekhov, A. G.; Trakhtengerts, V. Yu.; Manninen, J.; Turunen, T. (HAL CCSD, 2006)
International audience Using the data from satellite CRRES and three geostationary LANL spacecraft, the propagation of an electron cloud from midnight to the evening sector is investigated. An electron cloud was injected during a weak isolated substorm that developed on a quiet geomagnetic background. It is found that within the local time sector from 03:00 until at least 08:00 MLT, the propagation of electrons at perpendicular pitch-angles is well described by a simple model of drift in the dipole magnetic field. The flux levels in the field-aligned electrons increase simultaneously with the flux at perpendicular pitch angles, which is attributed to the pitch angle diffusion by the whistler mode. This pitch-angle diffusion leads to precipitation of electrons from a drifting cloud and an increase in the ionospheric electron density, simultaneously observed above Tromsø, Norway, by the EISCAT UHF radar in the morning sector (04:40?05:25 MLT). The precipitation develops as quasi-periodic pulses with a period of about 100 s. We discuss the models of pulsating precipitation due to the whistler cyclotron instability and show that our observations can be explained by such a model.